Challenges and opportunities in low-dimensional thermoelectric nanomaterials - Dong, Jinfeng (2023)
Thermoelectric materials can convert heat into electrical energy, which can potentially be used to improve the fuel efficiency of conventional heat engines. In recent decades, significant progress has been made in the thermoelectric field, where nanotechnology has played an important role. The quantum confinement effect has been shown to increase the Seebeck coefficient, while the nanostructures can effectively scatter phonons. In this review, the latest advances in thermoelectric nanomaterials were summarized and the challenges they face in thermoelectric-device fabrication were discussed. Firstly, the major problems hindering the development of nanowire-, thin-film-, and nanocrystal-based thermoelectric devices were discussed, followed by possible solutions in the subsequent sections. The unique carrier transport properties of one-dimensional nanowires that result from their distinct band structures were then examined. The distinct diffusive thermal transport, caused by boundary scattering of phonons, was also discussed. Next, the unique thermoelectric transport properties of superlattice thin films and two-dimensional electron gas were focused on. In addition, the different types of flexible thin films and strategies to improve their thermoelectric performance were described. Subsequently, the electrical transport properties of thermoelectric bulk samples consolidated from solution-processed nanocrystals, including the synthesis principles and modulation doping were discussed. Furthermore, the rational design of distinct microstructures which can selectively scatter phonons was elaborated on. Finally, we prospect for future developments in thermoelectric nanomaterials.